Body Appreciation, Self-Compassion, and Sexual Self-Consciousness in Women: The Example of Turkey and Azerbaijan - Deniz, M. Engin; Kurtulus, Hacer Yildirim; Rustamov, Elnur (SLOVAK ACAD SCIENCES, CTR SOCIAL & PSYCHOLOGICAL SCIENCES, IEP, 2024)
Especially women, due to cultural and societal expectations, are less responsive toward erotic stimuli when they are engaged with neutral and distractive thoughts and emotions. Focusing on a task-irrelevant context during sex adversely affects functioning. Therefore, this study aims to explore the pathway from body appreciation to sexual self-consciousness in women in Turkey and Azerbaijan. In addition, the mediating role of self-compassion on this path was also explored in the study. A total of 643 women agreed to participate in the study, which included 343 women from Turkey (Age M = 32.30, SD = 8.67, range 18-58) and 300 women from Azerbaijan (Age M = 30.96, SD = .93, range 18-58). Structural equation modeling was used to test the mediating relationship between the variables. The results demonstrated that body appreciation predicts self-compassion and sexual self-consciousness in both samples and self-compassion predicts sexual self-consciousness. Furthermore, self-compassion has a mediating role in the relationship between body appreciation and sexual self-consciousness. Body satisfaction can increase women's self-acceptance and self-compassion despite their shortcomings. The higher the self-compassion, the more women can focus on sex without being distracted.
Keywords: women; body appreciation; self-compassion; sexual self-consciousness; DISSATISFACTION IMPLICATIONS; APPEARANCE DISSATISFACTION; IMAGE; ESTEEM; OBJECTIFICATION; EXPERIENCES; SATISFACTION; ATTENTION; AROUSAL; ANXIETY; Psychology